Zika Virus and Patient Blood Management. (January 2017) - Goodnough, Lawrence T.; Marques, Marisa B.
Abstract : Sporadic Zika virus infections had only occurred in Africa and Asia until an outbreak in Micronesia (Oceania) in 2007. In 2013 to 2014, several outer Pacific Islands reported local outbreaks. Soon thereafter, the virus was likely introduced in Brazil from competing athletes from French Polynesia and other countries that participated in a competition there. Transmission is thought to have occurred through mosquito bites and spread to the immunologically naive population. Being also a flavivirus, the Zika virus is transmitted by the Aedes mosquito that is endemic in South and Central America that is also the vector of West Nile virus, dengue, and chikungunya. In less than a year, physicians in Brazil reported a many-fold increase in the number of babies born with microcephaly. Despite initial skepticism regarding the causal association of the Zika virus epidemic and birth defects, extensive basic and clinical research evidence has now confirmed this relationship. In the United States, more than 4000 travel-associated infections have been reported by the middle of 2016 to the Centers for Disease Control and Prevention. Furthermore, many local mosquito-borne infections have occurred in Puerto Rico and Florida. Considering that the virus causes a viremia in which 80% of infected individuals have no symptoms, the potential for transfusion transmission from an asymptomatic blood donor is high if utilizing donor screening alone without testing. Platelet units have been shown to infect 2 patients via transfusion in Brazil. Although there was an investigational nucleic acid test available for testing donors, not all blood centers were initially required to participate. Subsequently, the US Food and Drug Administration issued a guidance in August 2016 that recommended universal nucleic acid testing for the Zika virus on blood donors. In this report, we review the potentially devastating effects of Zika virus infection during pregnancy and its implication in cases of Guillain–Barre syndrome in adults. Furthermore, we urge hospital-based clinicians and transfusion medicine specialists to implement perisurgical patient blood management strategies to avoid blood component transfusions with their potential risks of emerging pathogens, illustrated here by the Zika virus. Ultimately, this current global threat, as described by the World Health Organization, will inevitably be followed by future outbreaks of other bloodborne pathogens; the principles and practices of perioperative patient blood management will reduce the risks from not only known, but also unknown risks of blood transfusion for our patients.